Kebijakan Pemerintah Jerman Menangani Peningkatan Angka Kriminalitas Pencari Suaka sebagai Dampak dari Open Door Policy - Muhmmad Al Ghifari; Marten Hanura (Journal of International Relations Diponegoro, 2018)
Germany is one of the favorite destinations for immigrants and asylum seekers seeking help because of the open door policy that began to be implemented in August 2015. This policy opens German borders for asylum seekers fleeing the wars that occurred in the Middle East such as Syria, Iraq and Afghanistan. Waves of asylum seekers are increasingly flooding Germany. This policy then began to have an impact, one of which began to increase the number of crimes committed by asylum seekers in Germany. The German government then issued a new policy to handle the impact that arose from previous policies by launching the StarthilfePlus aid program. This study finds that policies implemented to cope with the impact of open door policies that have previously been implemented are not yet effective. The ineffectiveness of this policy is due to the two objectives that not yet achieved yet. First, there are no increased in migrants voluntarily returning to their home country. Secondly, the increasing number of failed asylum seekers residing in Germany compared with before the policy was implemented.